Extension Delivery Systems - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Valera, J.B. et al (eds.), 1987. An Introduction to Extension Delivery Systems. Island Publishing House Inc, Manila ISBN 971 1007 08 8